2015
DOI: 10.1002/masy.201500065
|View full text |Cite
|
Sign up to set email alerts
|

Epoxy Elastomers Modified with Silsesquioxane

Abstract: Summary: This study aimed at investigating into possible applications of polyhedral oligomeric silsesquioxanes (POSS) as fillers of epoxy elastomers. Detailed studies were carried out for octakis [(3-glycidyloxypropyl) dimethylosiloxy] octasilsesquioxane (POSS-OG). The elastic epoxy materials consisted of diglycidyl ethers of 1,4-butanediol or 1,6-hexanediol, crosslinked with polyoxypropylenediamine Jeffamine D2000. The results obtained by differential scanning calorimetry (DSC), dynamic mechanical thermal an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
10
0

Year Published

2015
2015
2015
2015

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(10 citation statements)
references
References 23 publications
0
10
0
Order By: Relevance
“…In the article [37] it was also shown that the elastic modulus for structures oriented in a magnetic field increased from 10 9 to 10 10 Pa at temperatures of the order of 2408C. In the materials studied by us, a significant change of the elastic modulus (from 1.1 to 2.5Á10 9 Pa) at similar temperatures could be observed after adding the filler (POSS-OG) to the cured matrix [29].…”
Section: Introductionmentioning
confidence: 54%
See 4 more Smart Citations
“…In the article [37] it was also shown that the elastic modulus for structures oriented in a magnetic field increased from 10 9 to 10 10 Pa at temperatures of the order of 2408C. In the materials studied by us, a significant change of the elastic modulus (from 1.1 to 2.5Á10 9 Pa) at similar temperatures could be observed after adding the filler (POSS-OG) to the cured matrix [29].…”
Section: Introductionmentioning
confidence: 54%
“…In the first part of studies, a series of liquid crystalline epoxy compounds was synthesized; their properties were reported in paper [30]. Subsequently, the research scope was extended by introducing new epoxy monomers with longer aliphatic chains and curing them with the use of different curing agents [28,29,32,36]. The molecular structures of all the synthesized materials along with the temperatures of phase transitions during heating are shown in Table 1.…”
Section: Methodsmentioning
confidence: 99%
See 3 more Smart Citations